rano LITERARY TEXTS FOR IMPROVING READING AND WRITING SKILLS: LITERARY TEXTS FOR IMPROVING READING AND WRITING SKILLS - Norbekova, Ra’no (Журнал иностранных языков и лингвистики, 2022)
Literary texts serve quite effectively to improve learners’ reading skills and vocabulary knowledge. For example, the students who read literary texts showed more improvement in vocabulary and reading than those who read nonliterary texts.